Nilai Pendidikan Moral dalam Film 172 Days: Analisis Wacana Kritis Teun A. Van Dijk - Nurhikmah, Nurhikmah; Sumiyati, Sumiyati; Sukrisno, Sukrisno; Dewi, Hepta Pracipta; Charlina, Charlina (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
Films wield significant societal influence by imparting moral messages, particularly resonating with the millennial demographic. This study delves into the moral narrative of the true-story-based film "172 Days." Employing a qualitative descriptive approach, the research scrutinizes the macro, superstructure, and microstructure of the film. Through Teun Van Dick's Critical Discourse Analysis, the macro structure illustrates life's trials, emphasizing patience and sincerity. The superstructure emphasizes love for all things solely for the sake of Allah. Lastly, the microstructure advocates audience sincerity and patience in embracing their destiny. The findings underscore the film's profound message of resilience and faith, resonating with contemporary societal values. By analyzing the film's layers, this research sheds light on the nuanced ways in which cinema shapes moral consciousness and societal perceptions.